« Et si Félicité portait malheur ? » - Marie Scarpa (Flaubert: Revue Critique et Génétique)
Félicité, the perfect kind-hearted servant girl, is unfortunate. It is well known. But a certain “roughness” in the story challenges the rather smooth portrait (considering even her relationship to Loulou) that is usually drawn of this character. This “roughness” is confirmed and even emphasized in the “avant-textes”. Is Félicité so perfect in her role (thematic and anthropologic) of the “helping woman”? It seems that her relation to fate (bad luck) and to death (bad deaths) could be here reexamined.